Effect of a selection of skin penetration enhancers on topical anti-inflammatory effect of Boswellic acids in carrageenan-induced paw edema in rats - Valiollah Hajhashemi; Sadaf Safaei (Advanced Biomedical Research, 2021)
Background: Boswellia species have been used for treatment of chronic inflammatory disease. Several studies have documented the anti-inflammatory effect of Boswellic acids (BAs) after systemic administration. This study was aimed to evaluate the effect of some skin penetration enhancers on topical anti-inflammatory effect of BAs in rats. Materials and Methods: Male Wistar rats weighting 180–220 were used. Anti-inflammatory activity was assessed using carrageenan test. BAs dissolved in ethanol, propylene glycol 2%, 5%, olive oil and applied topically. Menthol, D-limonene, or eucalyptus oil 0.5%, 1% were also tested as other skin penetration enhancers and applied topically 30 min prior to subplantar injection of carrageenan into the right hind paw of rats. The volume of the paw was measured at 0 and 4 h after carrageenan with a digital plethysmometer and the difference was used as an index of inflammation. Piroxicam gel was used as a standard drug. Results: A 4% ethanolic solution of BAs showed significant anti-inflammatory effect. Propylene glycol (2% and 5%) in alcohol did not change the effect. Olive oil also enhanced penetration of BAs. Menthol 0.5%, 1% and D-limonene 0.5%, 1% did not show any significant change compared to olive oil alone. In the present study, eucalyptus oil 1% in olive oil was known as the best carrier for transdermal delivery of BAs. Conclusion: BAs have considerable topical anti-inflammatory effects and olive oil alone or especially in combination with eucalyptus oil can be promising vehicles for skin penetration of topical BAs.